The Influence of Work Discipline, Motivation, Organizational Culture, and Leadership Style on Employee Performance Galang District, Batam City - Martinus Buulolo; Yanto; Kepi Kusumayanti (Sinergi : Jurnal Ilmiah Ilmu Manajemen, 2023)
Organizations have quite serious challenges, namely managing, developing in achieving the end results of employee performance. Creative resources bring renewal, contribution to the interests of modern organizations at work. This study aims to determine the involvement of work discipline, motivation, organizational culture, and leadership style on employee performance. The approach used in research uses a quantitative descriptive approach. 69 respondents as data sources in this study were employees of Galang District, Batam City. The alternative method used to analyze this research is the Statistical Package for the Social Sciences (SPSS). Each variable is tested for validity, reliability test at the initial stage. Furthermore, the variables of work discipline, motivation, organizational culture, and leadership style will be tested on employee performancewhich is the second stage of testing. Work discipline is proven to have a positive and significant effect on employee performance in research, and organizational culture shows positive results and has a significant effect on employee performance, and leadership style shows positive and significant results on performance. Then work discipline has a negative and significant effect. Lastly, other findings about the relationship between work discipline, motivation, organizational culture, and leadership style show positive and significant results on their involvement in employee performance.